Cross-conjugation as a Motif for Organic Non-Linear Optical Molecules. Issue 1698 (19th August 2014) - Rawal, Meghana; Garrett, Kerry; Tillack, Andreas F.; Kaminsky, Werner; Jucov, Evgheni; Shelton, David P.; Timofeeva, Tatiana V.; Eichinger, Bruce E.; Robinson, Bruce H.; Dalton, Larry R.
ABSTRACT: We studied the effect of a cross-conjugated bridging group (χC) on charge-transfer in a push-pull chromophore system. The hyperpolarizability of such molecules was found to be comparable to that of a fully π-conjugated molecule (πC) with the same donor and acceptor. The cross-conjugated moiety was then applied as a pendant to a fully π-conjugated chromophore containing a tricyanopyrroline acceptor (TCP). The addition of a χC moiety did not alter the intrinsic hyperpolarizability and provides an avenue for extending and aiding πC systems. The molecules were examined by X-ray diffraction (XRD), hyper-Raleigh scattering (HRS) and UV-visible (UV-vis) spectroscopy. Experimental results were compared with the predictions of density functional theory (DFT). Cross-conjugated molecules have comparable β values, relative to πC molecules, due to reduced spatial overlap between the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO). Thus, the χC architecture could facilitate independent modification of donor and acceptor strengths while minimizing unfavorable effects on electronic transitions and dipole moments.